Is Rights Issue Will Raising the Stock Price of PT Nippon Indosari Corpindo Tbk? - Sylviana Maya Damayanti; David Anwar (University of Merdeka Malang, 2018)
The stock price of PT Nippon Indosari Corpindo Tbk (ROTI) declined due to the right issue announcement by the corporation, had caused the price of ROTI to fall from IDR 1,760 to IDR 1,195. As the price of the stock itself was in a volatile condition, it was interesting to understand more about the status of the stock price, whether it was undervalued or overvalued. The purpose of this study to calculated the fair share price of ROTI in 2017 based on the 2010-2016 historical data. The findings will be compared with the stock price in the market to know that ROTI was undervalued or overvalued for the decision of the investor to buy, hold or sell its shares. The valuation model used Constant-Growth Model or the Gordon Model. Based on the calculation the fair stock price were IDR 1,617.39, whereas when using the Gordon Model the fair share price were IDR 1,104.19 per share. Based on data from Bursa Efek Indonesia, the closing price for ROTI on December 30, 2016, were IDR 1,600 and it can be concluded that the stock price of ROTI was undervalued.JEL Classification: G11, G23DOI: https://doi.org/10.26905/jkdp.v22i3.2020